Caracterização molecular e grau de especialização de espécies do complexo fusarium solani em cafeeiro conilon - Rocha, Matheus Ricardo da (2020)
The genus Fusarium is one of the most economically destructible phytopathogenic groups to cultivated plants, WHERE diseases caused by these species are responsible for losses that cost the global agricultural economy billions. Species of this group were i